2016
DOI: 10.1515/pjvs-2016-0068
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Silymarin and Choline Chloride (Liver Tonics) in Preventing the Effects of Aflatoxin B1 in Bovine Calves

Abstract: Aflatoxins are secondary metabolites produced by Aspergillus spp. which are injurious to animals and humans The aim of this study was to determine the effects of aflatoxin B 1 (AFB 1 ) on Average Daily Feed Intake (ADFI), Average Daily Weight Gain (ADWG), haematological and serum biochemical responses of Bovine Calves and to determine the comparative efficacy of two different liver tonics against AFB 1 . Twenty seven calves were selected from herd and divided into 3 groups. All calves were fed with 1.0 mg/kg A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…According to Naseer et al [38], silymarin showed better results compared to choline chloride (liver tonics) in lowering the AFB1-induced serum aminotransferase, creatinine, and blood urea nitrogen. Silibinin has received much attention, but the negation of mycotoxins toxicity by silibinin has only been achieved on primary rat hepatocytes, isolated rat Kupffer cells, calves, and mice [37,38,[40][41][42].…”
Section: Mycotoxins Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Naseer et al [38], silymarin showed better results compared to choline chloride (liver tonics) in lowering the AFB1-induced serum aminotransferase, creatinine, and blood urea nitrogen. Silibinin has received much attention, but the negation of mycotoxins toxicity by silibinin has only been achieved on primary rat hepatocytes, isolated rat Kupffer cells, calves, and mice [37,38,[40][41][42].…”
Section: Mycotoxins Effectsmentioning
confidence: 99%
“…Silibinin, a major pharmacologically active compound, is a mixture of silybin A and silybin B. The studies of hepatoprotective effect of silymarin against fumonisin B1 (FB1) and aflatoxin B1 (AFB1) were performed in mice and bovine calves [37,38]. The FB1-induced hepatocyte damage was significantly diminished by the silymarin treatment.…”
Section: Mycotoxins Effectsmentioning
confidence: 99%
“…Aspergillus growth reduces the nutritional value of feed stuff by producing aflatoxin and allergenic spores (Naseer et al, 2016a(Naseer et al, , 2017b. In 1729, Antonio Micheli named genus Aspergillus for the first time and developed a major science, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Aflatoxins are the most toxic mycotoxins, produced by Aspergillus spp. (Aspergillus flavus and A. parasiticus) (Naseer et al, 2016;Hassan et al, 2015). Aflatoxicosis refers to the syndromes because of ingestion, skin contact or inhalation of fungal metabolites (Murugesan et al, 2015), leading to economic losses due to curtailed growth of young animals, reduce feed intake, abnormal nutrient absorption and metabolism (Storm et al, 2014).…”
Section: Introductionmentioning
confidence: 99%